Association of Serotonin2c Receptor Polymorphisms With Antipsychotic Drug Response in Schizophrenia - Li, Jiang; Hashimoto, Hitoshi; Meltzer, Herbert Y. (Frontiers in Psychiatry, 2019)
There is conflicting evidence for the association between genetic polymorphisms in the serotonin (5-HT)2C receptor (HTR2C) and response to antipsychotic drugs (APD) in schizophrenic patients. We tested the association between the HTR2C polymorphisms, Cys23Ser, -759C/T, and -697G/C, and response to APDs (mainly clozapine) in a six-month prospective study in 171 patients with schizophrenia. Ser23 was significantly associated with treatment response (positive symptoms, X2=7.540, p=0.01; negative symptoms, X2=4.796, p=0.03) in male patients only. A -759C-Ser23 haplotype was similar associated with positive (X2=6.648, p=0.01) and negative (X2=6.702, p=0.01) symptom improvement. Logistic regression, after controlling for covariates, also showed significant haplotypic associations. A meta-analysis of six studies for Ser23 and treatment response showed an overall odds ratio of 2.00 (95%CI, 1.38-2.91, p=0.0003) or 1.94 (95%CI, 1.27-2.99, p=0.0024) under fixed or random effect models. These results provide additional evidence that HTR2C polymorphisms are associated with treatment response to APD with HTR2C antagonism or inverse agonism, in male schizophrenic patients.